Sociodemographic and clinical characteristics associated with perinatal outcome in high and low cerebro-umbilical ratio groups - Husain, Mahzabin; Sarmin, Rubab; Imran Alam, Sheikh; Tasnim, Maliha; Akter, Salma; Ferdous Chowdhury, Jannatul; Aziz, Effat; Sultana, Tasnia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Perinatal morbidity and mortality are largely driven by preterm birth, intrauterine asphyxia from placental insufficiency, and complications related to operative deliveries and medication use. Therefore, this study aimed to assess the association between sociodemographic and clinical characteristics and perinatal outcomes across high and low cerebro-umbilical ratio groups. The aim of the study was to assess the association between sociodemographic and clinical characteristics and perinatal outcomes across high and low cerebro-umbilical ratio groups. Methods: This prospective cohort study at the department of obstetrics and gynecology, BIRDEM General Hospital, Dhaka (November 2022-February 2024) included 106 women at 29-38 weeks gestation undergoing third-trimester Doppler. Maternal (gestational age, delivery) and fetal outcomes (birth weight, APGAR, respiratory distress, FGR) were assessed in relation to C/U ratio (cutoff 1.01). Data were collected via questionnaire, examination, and ultrasound, analyzed in SPSS 26.0 (p<0.05). Results: C/U<1.01 was associated with lower education (24.0% versus 57.1% higher secondary), lower income (79,800 versus 68,357 BDT), higher BMI (35.1 versus 33.1 kg/m2), earlier delivery (33.9 vs 36.6 weeks), lower birth weight (1.9 versus 2.6 kg; 96% versus 12.5% LBW), more complicated outcomes (84.0% versus 21.4%), APGAR<7 (68.0% versus 19.6%), NICU admission (74.0% versus 21.4%), respiratory distress (60.0% versus 12.5%), and FGR (18.0% versus 0%). Maternal age, parity, and occupation were similar between groups. Conclusions: A low cerebro-umbilical ratio is strongly associated with adverse perinatal outcomes, including lower birth weight, earlier delivery, and increased neonatal complications.